Connect 4: A Novel Paradigm to Elicit Positive and Negative Insight and Search Problem Solving - Hill, Gillian; Kemp, Shelly M. (Frontiers in Psychology, 2018)
Researchers have typically defined insight as a sudden new idea or understanding accompanied by an emotional feeling of Aha. Recently, examples of negative insight in everyday creative problem solving have been identified. These are seen as sudden and sickening moments of realization experienced as an Uh-oh rather than Aha. However, such experiences have yet to be explored from an experimental perspective. One barrier to doing so is that methods to elicit insight in the laboratory are constrained to positive insight. This study therefore aimed to develop a novel methodology that elicits both positive and negative insight solving, and additionally provides the contrasting experiences of analytic search solving in the same controlled conditions. The game of Connect 4 was identified as having the potential to produce these experiences, with each move representing a solving episode (where best to place the counter). Eighty participants played six games of Connect 4 against a computer and reported each move as being a product of positive search, positive insight, negative search or negative insight. Phenomenological ratings were then collected to provide validation of the experiences elicited. The results demonstrated that playing Connect 4 saw reporting of insight and search experiences that were both positive and negative, with the majority of participants using all four solving types. Phenomenological ratings suggest that these reported experiences were comparable to those elicited by existing laboratory methods focused on positive insight. This establishes the potential for Connect 4 to be used in future problem solving research as a reliable elicitation tool of insight and search experiences for both positive and negative solving. Furthermore, Connect 4 may be seen to offer more true to life solving experiences than other paradigms where a series of problems are solved working toward an overall superordinate goal rather than the presentation of stand-alone and un-related problems. Future work will need to look to develop versions of Connect 4 with greater control in order to fully utilize this methodology for creative problem solving research in experimental psychology and neuroscience contexts.